1977
DOI: 10.1152/jn.1977.40.6.1281
|View full text |Cite
|
Sign up to set email alerts
|

Optical recording of neuronal activity in an invertebrate central nervous system: simultaneous monitoring of several neurons

Abstract: 1. Using an optical method for measuring membrane potential, we have been able to monitor action-potential activity simultaneously in 14 neurons of the supraesophageal ganglion of the barnacle. 2. Under favorable conditions, 4-mV synaptic potentials could also be detected optically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
165
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(168 citation statements)
references
References 10 publications
3
165
0
Order By: Relevance
“…Methods used for recording voltage-sensitive optical signals are similar to those described in detail elsewhere (Salzberg et al, 1977;Wu and Cohen, 1993;Keller et al, 1998). To wash out unbound dye, stained slices were perf used with AC SF for at least 15 min before initiating the optical recording.…”
Section: Methodsmentioning
confidence: 99%
“…Methods used for recording voltage-sensitive optical signals are similar to those described in detail elsewhere (Salzberg et al, 1977;Wu and Cohen, 1993;Keller et al, 1998). To wash out unbound dye, stained slices were perf used with AC SF for at least 15 min before initiating the optical recording.…”
Section: Methodsmentioning
confidence: 99%
“…Voltage-sensitive dyes are notorious for the photo-dynamic damage they produce in neuronal plasma membranes (Salzberg et al, 1977). Under some conditions, they are known to cause significant changes in membrane biophysical properties, such as action potential broadening (Antic et al, 1999).…”
Section: Are Basal Spikelets Artifacts Of Voltage-sensitive Dyes?mentioning
confidence: 99%
“…The advantages of optical recording of membrane potential changes over more traditional techniques were recognized long ago by Salzberg et al (1977). Some of these include: (1) recording from inaccessible membranes, (2) preservation of mechanical integrity of the plasma membrane, and (3) the capability of recording simultaneously from very many points in an image.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent evidence from both vertebrates and invertebrates has suggested that nervous systems may function in a distributed manner with many neurons involved in even simple behaviors and most neurons functioning in more than one behavior. Optical recordings using voltage-sensitive dyes can simultaneously monitor the action potential activity of many neurons (Salzberg et al, 1977;Grinvald et al, 198 1;Zecevic et al, 1989;Nakashima et al, 1992) and may thus be useful in discriminating between these two kinds of neuronal organization. The most complete recordings from the Aplysia abdominal ganglion can detect the spike activity of about 50% of the 900 neurons present in the ganglion (Coggeshall, 1967;Cash and Carew, 1989).…”
mentioning
confidence: 99%